PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT AYOCONNECT TEKNOLOGI INDONESIA DI DKI JAKARTA - Inva Jaswita, Derizka; Kumala Putri, Novia (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of product quality and service quality both partially and simultaneously on customer satisfaction at PT Ayoconnect Teknologi Indonesia. The research is quantitative with hypothesis testing. The population in this study was customers of PT Ayoconnect Teknologi Indonesia and the number of samples based on Slovin was 124 respondents, sampling using a convenience sampling technique. Data collection methods are through questionnaires with a Likert scale, observation, and literature study. The research results obtained: (1) There is a positive and significant influence between product quality and customer satisfaction at PT Ayoconnect Teknologi Indonesia. The linear regression model Y = 5.140 + 0.566X1, and the calculated t value is 12.152 (> t table) with a sig value. 0.000 (> t table). (2) There is a positive and significant influence between service quality on customer satisfaction of PT Ayoconnect Teknologi Indonesia. Simple linear regression model Y = 6.832 + 0.423X2, and the calculated t value is 11.289 (> t table) with a sig value. 0,000. (3) There is a positive and significant influence between product quality and service quality simultaneously on customer satisfaction of PT Ayoconnect Teknologi Indonesia. Multiple linear regression model Y = 4.179 + 0.359X1+ 0.197X2, as well as a calculated F value of 85.034 (> F table) and a sig value. 0.000 (<0.05)